The impact of agriculture finance on small and medium agribusiness in Zambia: the case of Zambia National Farmers' Union - Lima Credit Scheme - Muyangwa, Nambwenga (Research of GSB, 2017)
The aim of the study is to assess the Impact of Agricultural Finance on Small and Medium Agribusiness in Zambia focusing on Lima Credit Scheme of the Zambia National Farmers Union (ZNFU) in sampled districts. Survey questionnaires were administered to 120 farmers selected from 8 districts. Two focus group discussions were held and key informants drawn from ZNFU, Zambia National Commercial Bank and representatives of the Agribusiness chamber and Insurance companies were interviewed. The study hypothesis that the LCS intervention has had no favourable impact on beneficiary farmers and Agro-Businesses in Zambia was proved to be null. To the contrary, the findings indicate that LCS had favourable impact on beneficiary farmers and Agro-Businesses in Zambia. Thus, the study findings show that to a greater extent the scheme had positive impact that include; increased knowledge among Lima Credit scheme beneficiaries through trainings in various topics such as financial literacy and crop husbandry, increased economic wellbeing of the LCS beneficiaries, more households procuring oxen drawn agricultural implements, higher production levels of maize and soy-bean, greater participation in the market by SSFs, increased income, among others. In addition to the descriptive analysis, the factor analysis too showed that the first factor access to production inputs based benefits suggests that in this component farmers accrued benefits from LCS which include access to market information, increase in area planted, increase in volumes sold and incomes. The second factor improved income based benefits suggests that respondents in this component acknowledges that as a result of increased incomes, they have recorded improved access to health, able to reinvest in other businesses, increase yield per hectare, able to pay loans on time, able to acquire agriculture Assets-Ox drawn, access to commodity markets and improved access to education. Unique to the scheme is the insurance cover on the loan amount that mitigates defaults resulting from natural cause such as drought and floods. The study concludes that Lima Credit Scheme had favourable impact on beneficiary farmers and Agro-Businesses in Zambia.